Genome-Wide Changes of Regulatory Non-Coding RNAs Reveal Pollen Development Initiated at Ecodormancy in Peach - Yu, Jiali; Bennett, Dennis; Dardick, Christopher; Zhebentyayeva, Tetyana; Abbott, Albert G.; Liu, Zongrang; Staton, Margaret E. (Frontiers in Molecular Biosciences, 2021)
Perennial trees protect themselves from harsh winter conditions by entering endodormancy. After a sufficient period of chill, the trees transit to ecodormancy and become capable of reactivating growth in favorable conditions. To study the function of regulatory non-coding RNAs in winter dormancy release, we analyzed the small RNA and long non-coding RNA (lncRNA) expression from peach (Prunus persica) floral buds in endodormancy (at 0 and 500 chill hours), ecodormancy (at 1000 chill hours) and bud break (3 and 7 days in a warm greenhouse after 1000 chill hours) stages. Small RNAs underwent a major shift in expression primarily between dormancy and flowering with specific pairs of microRNAs and their mRNA target genes undergoing coordinated differential expression. From endodormancy to ecodormancy, ppe-miR6285 was significantly upregulated while its target gene, an ASPARAGINE-RICH PROTEIN involved in the regulation of abscisic acid signaling, was downregulated. We also showed that ppe-miR2275, a homolog of meiosis-specific miR2275 across angiosperms, was significantly upregulated at ecodormancy, supporting microsporogenesis in anthers occurring at a late stage of dormancy. We identified 785 lncRNAs that, unlike the overall expression pattern in the small RNAs, demonstrated distinctive expression signatures across all dormancy and flowering stages. We predicted that a subset of lncRNAs were targets of microRNAs and found 18 lncRNA/microRNA target pairs with both differentially expressed across time points. The genome-wide differential expression and network analysis of non-coding RNAs and mRNAs from the same tissues provide new candidate loci for dormancy regulation and suggest complex noncoding RNA interactions control transcriptional regulation across these key developmental time points.